Ilmu Kalam Tinjauan Ilmu Kalam Pemikiran Ulama Modern Menurut Muhammad Iqbal - Khalimatus Fhadila, Annisa; Umi Nurul Hidayati; Hilmi Hidayatul; Maula Khainuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article explores the thoughts of Muhammad Iqbal, a modern scholar, in the context of Islamic theology (kalam), utilizing library research methods and a qualitative approach. Iqbal emphasizes the importance of revitalizing and reconstructing Islamic theology to face modern challenges and address the limitations of classical kalam thought, which he finds overly speculative. He critiques the classical approach dominated by metaphysical speculation and deductive argumentation, advocating for a more relevant approach to human and social issues. This research is analytical and takes an emic perspective, where data is obtained based on conceptual and theoretical facts from analyzed literature. Iqbal introduces the concept of the ego as the center of human life organization and stresses the importance of creative activity as part of divine activity. Iqbal's ideas inspire the development of a more anthropocentric and responsive kalam to contemporary Western discourse and socio-political issues.